The Influence Of Management Policies Through Work Motivation On Employee Performance In The Agriculture And Food Security Service And Fisheries Of Dairi Regency - Wandi Bron Ohto Tumanggor; Mesra B (Yayasan Multidimensi Kreatif, 2025)
This study aims to analyze the influence of Management Policy on Employee Performance by considering the role of Job Motivation and Job Satisfaction as intervening variables. The research was conducted on employees at the Dairi Regency Agriculture, Food Security and Fisheries Office with a sample of 131 employees out of 235 employees taken using purposive sampling. This study uses a quantitative approach and the Partial Least Squares (PLS) analysis method. The results of the study show that the Management Policy has a positive and significant influence on Employee Performance, with a T-Statistic value of 6.152 > 1.96 and a P-Value of 0.000 < 0.05, which indicates that a better management policy will improve employee performance. In addition, Management Policy also has a significant impact on Work Motivation, with a T-Statistic of 58.557 > 1.96 and a P-Value of 0.000, indicating the importance of management policies in building employee motivation. Other results showed that Work Motivation had a significant influence on Employee Performance with a T-Statistic of 6.959 > 1.96 and a P-Value of 0.000. These findings underscore that increased work motivation contributes to improved performance. Further analysis found that Management Policy has an indirect influence on Employee Performance through work motivation, with a T-Statistic of 7.028 and a P-Value of 0.000. This shows that work motivation plays a role as a mediating variable that strengthens the relationship between Management Policy and Employee Performance, so that effective management policies can have more impact if accompanied by increased work motivation. Recommendations are given to organizations to continue to develop management policies that are able to increase motivation and job satisfaction for the optimization of employee performance.